Village Economic Development Through Strengthening the Legality of BUMDES in Dringu Village, Probolinggo Regency - Erdianti, Nela; Ilham Ramadhan, Muhammad Rizqi Hilal; Fitriana, Zuhda Milla; Rahmatin, Leily Suci (International Journal of Community Service Implementation, 2023)
Efforts to improve the national economy will be achieved through economic success at the regional level, supported by economic activities at the smallest regional level, namely the village, which also has a direct impact on community welfare. Community service activities are carried out in the Dringu Village area, Dringu District, Probolinggo Regency. The research was conducted using a qualitative analysis method with a descriptive approach, where the focus of this research is efforts that can be made to enforce the legality of Village-Owned Enterprises so that the original income of Dringu village increases. Village-Owned Enterprises (BUMDes) are one of the economic institutions that were built based on community initiative and adhere to the principle of independence and aim to develop rural areas which can be achieved through community empowerment with the aim of increasing the productivity and diversity of existing businesses. In principle, the legal basis for establishing BUMDes is in Article 87 paragraph (1) of the Village Law, Article 132 paragraph (1) of Village Government Regulations and Article 4 of Permendesa PDTT No. 4 of 2015 concerning the Establishment, Management and Dissolution of BUMDes. Therefore, as an effort to implement the laws and regulations mentioned above, the UPN "Veteran" Jawa Timur Service Team organized and carried out community service activities regarding "Socialization and Assistance for the Legality Documents for the Establishment of BUMDES in Dringu Village, Dringu District, Probolinggo Regency in order to improve the welfare of the community in Dringu Village